I cannot do that…I'm a counsellor: Implications of professional boundaries on counsellors' public life as entertainers. Issue 2 (24th May 2021) - Decelis, Karen; Falzon, Ruth
Abstract: Background: This study explores perceptions regarding counsellors who are also public entertainers, an issue on which there is a dearth in literature and in codes of ethics. For this study, we reviewed three codes of ethics: the 2014 American Counselling Association's (ACA), the 2017 British Association for Counselling and Psychotherapy's (BACP) and the 2011 Malta Association for the Counselling Profession's (MACP). Method: The research question begged a qualitative approach using individual, audio‐recorded, semi‐structured interviews with twelve participants: six counsellors and six non‐counsellors. Thematic analysis was selected as the most appropriate methods for analysis. Findings: Participants think that counsellors can be entertainers during their free time, but need strict boundaries and ethical responsibility whilst following Rogers' (1957, 1980) person‐centred skills of being non‐judgemental, empathic and congruent. Boundaries, the context of a small‐island community, public life, self‐disclosure, wellbeing and challenges were all major themes elicited. Counsellor participants (CPs) highlighted that there is no guide Maltese counsellors can follow regarding what they can and cannot do in public as public entertainers. Participants noted that in the local context, counsellors need to be careful about disclosing their opinions regarding Politics and political affiliations. Politics seemed to be of particular concern and reflects the local biparty culture often loaded with emotions and very strong opinion and allegiances. Participants also reflected that the status of an entertainer/counsellor can also help publicise the profession in the best interest of wellbeing and the profession. Implications for Practice: Implications for practice include training courses with opportunities for reflection on what counsellors can/not do in public in order to continuously address boundaries; training on social media behaviour; training on specialised ethical issues around being a counsellor/entertainer through continuing professional development sessions; specialised training for supervisors; issues to be address in contacts with clients; and updated codes of ethics/ethical framworks. Conclusion: Recommendations include personal reflection and supervision, training at master's level, continued professional development, revised codes of ethics and ethical guidance by qualified supervisors. This study was a master's dissertation submission, where Karen was the supervisee and Ruth the supervisor.